PENGARUH KUALITAS, HARGA DAN PROMOSITERHADAP KEPUASAN KONSUMEN PRODUK HNI HPAI DI BUSSINESS CENTER 2 BATAM - Ermida, Ermida; Syaifullah, Syaifullah (SCIENTIA JOURNAL, 2019)
This study aims to determine how the influence of quality, price, and promotion on consumer satisfaction HPAI HNI products. The object of this research was conducted at the Batam Business Center 2. Data collection techniques, using measuring instruments in the form of questionnaires as many as 101 respondents were distributed to members or consumers who use HPAI HNI products. The analysis technique used is the validity test, reliability test, and hypothesis significance test using SPSS version 21. Based on the hypothesis test it can be seen that the variables of quality, price and promotion in the regression model are 83.1% while the remaining 16.9% variables are satisfaction consumer (Y). From the discussion of the results of the questionnaire it can be concluded that HNI products are needed by consumers, the packaging form of HPAI HNI products is very safe and easy to carry everywhere, there is an expiration date, prices are in line with the benefits of HPAI HNI products so consumers feel satisfied, with the promotion of interested consumers to buy, and products can meet the Muslim market. Research results show that quality, price and promotion of customer satisfaction have a significant influence on consumer satisfaction of HPAI HNI products at Batam Business Center 2.